Design, fabricate and analysis of tremor test rig to emulate human hand tremor - Jamaludin, H.; Eng, K. S.; As'arry, A.; M. Rezali, K. A.; Raja Ahmad, R. K.; Md Zain, M. Z. (AIP Publishing LLC, 2022)
People with various ages might experience Parkinson's disease. However, the chances for people to experience the Parkinson's disease might increases as the age grew older. As for now, Parkinson's disease had no definite cure and only treatments of various kinds could help to relieve some of the symptoms that occurred from the Parkinson's disease. Active elements such as actuators as the anti-tremor devices could be used. In initial stage in developing the anti-tremor device, a tremor test rig which could help to emulate the hand tremor was used. For this study, a tremor test rig had been designed to emulate the vibration of the tremor of Parkinson's disease. With the used of design specification method, three conceptual designs of the tremor test rig were developed and the design that had the highest score (Pugh Chart) was chosen to be the final design of the tremor test rig. Based on the detailed design, the tremor test rig was fabricated. The tremor hand model acceleration was being measured and being converted into Power Spectral Density (PSD) using Fast Fourier Transform (FFT) in which the highest peak of PSD was the frequency of tremor vibration. The tremor test rig's accuracy was being analyzed by making a comparison with the frequency of the vibration from the test rig and the theoretical tremor vibration frequency. From this research study's results, it can be observed that the frequencies of the actual tremor data that been collected from PD patients across 4 subjects are all at the range of 2-4 Hz and one frequency is at 3.784 Hz as the most severe tremor frequency from subject 3 at y-axis. Meanwhile, the results from the data imitation shows that percentages of errors are ranged from 10% to 40% across 5 PD subjects with the highest was at 39.50% for subject 5. Thus, it shows that the tremor test rig cannot perfectly replicate the actual tremor. Nevertheless, all results can be considered as acceptable and valid as the results are in the frequency range of theoretical actual tremor. In future, the test rig could be modified to vibrate in three-dimensional to emulate the hand tremor in a more precise manner.